2018
DOI: 10.1159/000492336
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease in Idiopathic Pulmonary Fibrosis: Uncertainties and Controversies

Abstract: The mechanisms of idiopathic pulmonary fibrosis (IPF), a rare, devastating disease with a median survival of 3–5 years, are not fully understood. Gastroesophageal reflux disease (GERD) is a frequent comorbidity encountered in IPF. Hypothetically, GERD-associated microaspiration may lead to persistent inflammation impairing lung infrastructure, thereby possibly accelerating the progression of IPF. IPF may increase intrathoracic pressure, which can aggravate GERD and vice versa. On the basis of the possible bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…In addition, dysphagia is a rare manifestation in both AAV 52 and sarcoidosis 53 . Whereas, it is suggested that gastroesophageal reflux disease (GERD)-associated microaspiration may lead to the progression of idiopathic pulmonary fibrosis (IPF) and IPF may increase intrathoracic pressure, which can aggravate GERD vice versa 54 . GERD is a common problem in sarcoidosis 55 , but not in AAV 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dysphagia is a rare manifestation in both AAV 52 and sarcoidosis 53 . Whereas, it is suggested that gastroesophageal reflux disease (GERD)-associated microaspiration may lead to the progression of idiopathic pulmonary fibrosis (IPF) and IPF may increase intrathoracic pressure, which can aggravate GERD vice versa 54 . GERD is a common problem in sarcoidosis 55 , but not in AAV 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study of 105 SSc patients, our group did not find that esophageal involvement measured by manometry was a prognostic factor for ILD progression . Consistently in IPF, the link between GERD and ILD remains controversial . Deciphering the relationships between GERD and ILD remains critical in SSc, but also in ILDs overall, and further investigation to clarify this issue is warranted.…”
mentioning
confidence: 66%
“…Breathing appears as the more frequent problem followed by sleep disorders. In the literature breathing was associated with gastroesophageal reflux [23], high fat disease [24] and obesity [25].…”
Section: Discussionmentioning
confidence: 99%